Evaluation and Comparison of Short Form Methadone Maintenance Treatment Training Courses Among Iranian General Physician and Psychologist Participants. (January 2022) - Saberi Zafarghandi, Mohammad Bagher; Dadfar, Mahboubeh; Arezoomandan, Reza; Veisy, Fateme; Behnood Rod, Azin
The evaluation of the effectiveness of education plays an important role in the improvement of training processes. The aim of the present study was to evaluate and compare the short form training courses for methadone maintenance treatment (MMT) in Iranian general physicians (GPs) and psychologists. This was a descriptive cross-sectional study with 203 participants (91 GPs and 112 psychologists) in three 10-day short form MMT training courses at the School of Behavioral Sciences and Mental Health - Tehran Institute of Psychiatry. After the courses, participants were asked to complete the Kirkpatrick Training Evaluation Questionnaire. Overall, the GPs evaluated the short form MMT training course significantly more positively than did the psychologists. Evaluation scores for Levels 1, 2, and 4 were good, average, and average, respectively. The Level 2 (learning) scores of both GPs and psychologists increased after the short form MMT training course compared with before the short form MMT training course. Similarities in the views of the GPs and the psychologists were more than differences between them. Research findings raised concerns about the implementation, management, monitoring, new guidelines, support, and training for this training course while providing valuable information in helping to facilitate more involvement of GPs and psychologists in the short form MMT training course.